Trimelopter crispolanatum (Asparagaceae, Scilloideae), a new species from Namaqualand, South Africa - Martínez-Azorín, Mario; Crespo, Manuel B.; Alonso-Vargas, María Ángeles; Pinter, Michael (Phytotaxa, 2020)
Hyacinthaceae subfam. Ornithogaloideae (= tribe Ornithogaleae of Aparagaceae sensu APG 2009, 2016, Chase et al. 2009) includes about 300 species of bulbous plants mainly distributed throughout Europe, Africa and south-west Asia. The latest comprehensive study in Ornithogaloideae (Martínez-Azorín et al. 2011) demonstrates the existence of 19 monophyletic genera which are characterised by a clear syndrome of morphological characters related to biogeographic patterns.